Analysis of The Correlation Between Gratitude and Emotional Intelligence Among University Students - Achmad, Adang Darmawan; Qotadah, Hudzaifah Achmad; Qubro, Hanna Safira El (PT. Riset Press International, 2023)
People with a high level of emotional intelligence can keep their feelings under control, both towards other people and towards themselves. As a result, it has been discovered that practicing gratitude can help students improve their emotional intelligence. This research aimed to investigate the connection between being grateful and having high levels of emotional intelligence among students. The investigation utilized a quantitative method and a design based on correlation. This research was carried out with the participation of 91 total students. Two scales were used in the data collection: a 15-item Emotional Intelligence Scale and the Development and Validation of the Islamic Gratitude Scale (IGS-10), created by Ahmad Rusdi in 2021 to measure thankfulness. The analysis of the data showed that gratitude and emotional quotient are positively correlated with one another. This suggests that greater levels of gratitude are connected with greater levels of emotional intelligence; hence, this demonstrates that gratitude can increase students' emotional intelligence and should be emphasized in educational settings.